Scaffolding MATLAB and octave software comprehension through visualization - Lessa, I. (2022)
Multiple view interactive environments (MVIEs) provide visual resources to support the comprehension of a specific domain dataset. For any domain, different views can be selected and configured in a real time fashion to be better adjusted to the user needs. This paper focuses on the use of a MVIE called OctMiner to support the comprehension of MATLAB and GNU/Octave programs. The authors conducted a case study to characterize the use of OctMiner in the context of comprehension activities. Results provide preliminary evidence of the effectiveness of OctMiner to support the comprehension of programs written in MATLAB and Octave.